Beam spreading and wander of partially coherent Lommel–Gaussian beam in turbulent biological tissue. (September 2018) - Yu, Lin; Zhang, Yixin
Highlights: Beam spreading and wander of vortex beam are investigated in turbulent biological tissue. Wigner distribution function is used to establish the spreading and wander model of Lommel–Gaussian vortex beam. Tissue turbulence effect and beam parameter optimization are discussed. The results are beneficial for biomedical applications based on light propagation in tissue. Abstract: Aiming at the partially coherent Lommel–Gaussian beam, we investigate its propagation in turbulent biological tissue. By use of Wigner distribution function, a theoretical model is constructed to describe turbulence induced beam wander and long-term spreading. We analyze the effects of tissue parameters including the fractal dimension D, strength coefficient S of refractive-index fluctuation, small length-scale factor l 0 and characteristic length lc of heterogeneity. We find that beam suffers less turbulence interference in tissue with smaller D, S, lc and larger l 0 . As for beam optimization, Lommel–Gaussian beam with low-order vortex and moderate waist width is preferable. The beam symmetry can be arbitrary, but incoherent beam with long wavelength is undesirable. The theoretical model and results give useful references for investigations of light propagation in tissue and biomedical applications of vortex beam.